Nucleation and crystal growth control for scalable solution-processed organic–inorganic hybrid perovskite solar cells. Issue 4 (3rd January 2020) - Hu, Hanlin; Singh, Mriganka; Wan, Xuejuan; Tang, Jiaoning; Chu, Chih-Wei; Li, Gang
Abstract : In this review, we provide an in-depth overview of perovskite film formation mechanism and highlight the important role of nucleation/crystal growth in perovskite photovoltaics by using scalable solution deposition techniques. Abstract : Over the past decade, intensive research efforts have been directed toward the field of organic–inorganic hybrid perovskites, with dramatic progress made in both the photovoltaic performance and device stability. Therefore, it has become the fastest growing photovoltaic research area. Perovskite materials use low-cost earth-abundant elements and can be solution-processed; furthermore, the technology is compatible with large-scale roll-to-roll manufacturing. Recently, the successful demonstration of the photovoltaic performance of perovskites reaching that of the commercialized monosilicon photovoltaic technology combined with the significantly improved stability has made scaling-up the perovskite PV technology to become a new research area, which is the topic of this review. First, the fundamental background knowledge of classical nucleation and crystal growth from a solution is summarized along with its application in perovskite film evolution. We then discuss the common perovskite PV device architectures and perovskite layer deposition methods, followed by summarizing scalable solution approaches with recent progress and related challenges for the scaling-up process. Upon the introduction of the current in-depth understanding of perovskite nucleation and crystal growth, external strategies (including both physical and chemical approaches) controlling the perovskite film formation are reviewed in diverse scalable manufacturing methods. Overall, aiming at overcoming the challenges of transferring from laboratory research, we provide an overview of achieving high-performance perovskite solar cells by using scalable fabrication methods via precise nucleation and crystal growth control during the perovskite film formation process.